Economic mobility across generations: Old versus new EU member states - Roy van der Weide; Ambar Narayan; Mario Negre (Deutsches Institut für Entwicklungspolitik (DIE), 2019)
A country where an individual's chances of success depend little on the socio-economic success of his or her parents is said to be a country with high relative intergenerational mobility. A government's motivation for seeking to improve mobility is arguably two-fold. There is a fairness argument and an economic efficiency argument. When mobility is low, it means that individuals are not operating on a level playing field. The odds of someone born to parents from the bottom of their generation will be stacked against him or her. This is not only unfair but also leads to a waste of human capital, as talented individuals may not be given the opportunity to reach their full potential. Reducing this inefficiency will raise the stock of human capital and thereby stimulate economic growth. Since the waste of human capital tends to be concentrated toward the bottom of the distribution, the growth brought about by mobility-promoting policy interventions tends to be of an inclusive nature, in line with the spirit of Sustainable Development Goal (SDG) 10 on reducing inequality. For large parts of the world's population, individual education is still too closely tied to the education of one's parents, and there is a clear divide between the high-income and developing world. The patterns observed globally are also observed within Europe. Intergenerational mobility (or equality of opportunity) is visibly lower in the new member states (i.e. Eastern Europe), where national incomes are lower. Raising investment in the human capital of poor children towards levels that are more comparable to the investment received by children from richer families will curb the importance of parental background in determining an individual's human capital. Countries at any stage of development can raise intergenerational mobility by investing more to equalise opportunities. The evidence strongly suggests that public interventions are more likely to increase mobility when: a) public investments are sufficiently large, b) are targeted to benefit disadvantaged families/ neighbourhoods, c) focus on early childhood, and d) when there is a low degree of political power captured by the rich.
Keywords: 330